Social Environmental Responsbility (CSR) as a Legal Obligation in Corporate Law: Implementation and Its Impact on Society - Imam Nur Hidayat Tarigan; Ivana Novrinda Rambe; Yessi Kurnia Arjani Manik (PT ARFA DIGITAL TECHNOLOGY, 2025)
Specifically, the study identifies a crucial legal gap: the limited scope of this obligation only to natural-resource-based companies, and critically analyzes the disproportionality of legal sanctions that undermines its deterrent effect. Initially recognized as a voluntary, ethics-driven initiative, TJSL has now become a legal mandate for certain limited liability companies, especially those engaging in or related to natural resources. This shift creates a distinctive paradigm compared to neighboring Southeast Asian countries, which mostly prefer incentive-based or voluntary frameworks. The study aims to analyze in depth the juridical construction of TJSL as a mandatory obligation, identify primary challenges in its implementation and governance, and examine the legal enforcement and empirical implications of such regulation for the community in the context of sustainable development. Findings highlight legal gaps, particularly the limited scope of the obligation to only natural-resource-based companies, ambiguities in operational definitions and funding sources, and weaknesses in the effectiveness of legal sanctions. The research suggests the need for comprehensive regulatory reforms to ensure the effectiveness of TJSL both legally and empirically for Indonesian society as a whole